Self Efficacy Teknologi Mahasiswa Akuntansi : Ditinjau dari Minat dan Tingkat Kecemasan terhadap Komputer - Habsyah Fitri Aryani; Mariska Nur Hanifah; Sintia Nur Afifah; Muhammad Aras Prabowo (Economics and Business Faculty UNUSIA, 2025)
This study aims to analyze the effects of students’ interest and computer anxiety on students’ self efficacy in using the Accurate accounting application. The study is motivated by the growing importance of accounting technology competence in the digital era, where students’ confidence in using accounting software is influenced by psychological factors. The scope of this research is explicitly limited to accounting students who have used the Accurate application in academic coursework, focusing on three main variables: students’ interest, computer anxiety, and self efficacy. A quantitative associative approach was employed, with data collected through questionnaires distributed to accounting students. The data were analyzed using multiple linear regression with the assistance of SPSS. The results indicate that students’ interest has a positive but insignificant effect on self-efficacy (p = 0.242), while computer anxiety has a positive and significant effect on self-efficacy (p = 0.024). Simultaneously, both variables influence self efficacy; however, their explanatory power is relatively low (Adjusted R² = 0.098). These findings suggest that students self efficacy in using the Accurate application is more strongly influenced by their level of computer anxiety than by learning interest alone. Therefore, learning strategies aimed at reducing computer anxiety such as hands on training, intensive guidance, and a supportive learning environment are essential to enhance students self efficacy in accounting technology utilization.